2019
DOI: 10.1080/13669877.2019.1691858
|View full text |Cite
|
Sign up to set email alerts
|

The Potsdam radon communication manifesto

Abstract: Risk communication efforts to mitigate the second cause of lung cancer worldwide (after tobacco smoking)the radioactive gas radon in buildingsare often ineffective. Therefore, new European legal requirements bind member states to prepare communication strategies to ' … increase public awareness and inform local decision makers, employers and employees of the risks of radon … ' (Council directive 2013/59/EURATOM, ANNEX XVIII/(10)). This manifesto is written to support states to prepare an effective and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…Furthermore, the extensive attention spa websites put on radon's natural origins and characteristics stands in contrast to recent advice formulated for those designing health campaigns. This latter advice builds on the notion that people "perceive technological threats to be more risky than natural threats" [34], and hence stresses that "risk communicators need to draw attention to radon" not as a natural gas, but rather as a major cause of "indoor air pollution" [35]. Thirdly, radon spa websites mostly provide implicit and non-visual references to radon risk (if any), while health campaigns contain numerous explicit references to the lung cancer risk associated with radon, often supported by various visuals (see e.g., the websites of the 2021 US radon awareness week https://www.cdc.gov/radon/awareness.html, the 2021 European radon week https://radoneurope.org/event/european-radonweek-2021/, or the 2020 UK radon awareness week https:// radonweek.co.uk/).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extensive attention spa websites put on radon's natural origins and characteristics stands in contrast to recent advice formulated for those designing health campaigns. This latter advice builds on the notion that people "perceive technological threats to be more risky than natural threats" [34], and hence stresses that "risk communicators need to draw attention to radon" not as a natural gas, but rather as a major cause of "indoor air pollution" [35]. Thirdly, radon spa websites mostly provide implicit and non-visual references to radon risk (if any), while health campaigns contain numerous explicit references to the lung cancer risk associated with radon, often supported by various visuals (see e.g., the websites of the 2021 US radon awareness week https://www.cdc.gov/radon/awareness.html, the 2021 European radon week https://radoneurope.org/event/european-radonweek-2021/, or the 2020 UK radon awareness week https:// radonweek.co.uk/).…”
Section: Discussionmentioning
confidence: 99%
“…There is a legal requirement in the EU member states to increase public awareness, and to inform local decision makers, employers and employees of the risks of radon, including in relation to smoking [ 11 ]. Moreover, the EU member states shall provide, as appropriate, approaches for the involvement of stakeholders in decisions regarding the development and implementation of strategies to manage exposure situations.…”
Section: Some Gaps In Existing National Radon Control Strategiesmentioning
confidence: 99%
“…Efforts to communicate the risks of radon and behavioural recommendations to avoid them have many gaps, and are limited in various aspects. Bouder et al pointed out that recommended radon communication, as organised by authorities, is still often not evidence-based, theory-based nor strategic [ 11 ]. The results of a systematic review of health communication campaigns in the field of radon found that, although not recommended, an informative tone of voice (factual, scientific and numerical information) in radon communication prevails.…”
Section: Some Gaps In Existing National Radon Control Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of communication with stakeholders, including the population, is supposed to be an integral part of national radon programs. The problem of low public awareness of radon and the health risk it poses is still typical for many countries [9][10][11][12][13][14][15][16], including the Russian Federation. This leads to the fact that there is no market for radon protection and remediation of buildings in our country yet [17].…”
mentioning
confidence: 99%